2010
DOI: 10.1016/j.rmed.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of health care-associated pneumonia in a Korean teaching hospital

Abstract: Severity of illness, rather than type of pneumonia, was the main predicting factor for in-hospital mortality among patients with pneumonia hospitalized through the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
64
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 19 publications
10
64
4
Order By: Relevance
“…The three most widely studied criteria for severe pneumonia are the 20-variable Pneumonia Severity Index 20 , the 5-variable CURB-65 score the score is an acronym for each of the risk factors : Confusion, Urea 7 mmol / L, Respiratory rate ≥ 30 / min, low blood pressure, and Age ≥ 65 21 , and the 8-variable IDSA / ATS criteria 6 . We analyzed this study in accordance with the 8-variable IDSA / ATS criteria 6 , which is reported to have similar prognostic power to the Pneumonia Severity Index 20 in HCAP patients 22 , and disease severity on admission was identi ed as a prognostic factor for mortality from HCAP, as previously reported 23 .…”
Section: Discussionmentioning
confidence: 81%
“…The three most widely studied criteria for severe pneumonia are the 20-variable Pneumonia Severity Index 20 , the 5-variable CURB-65 score the score is an acronym for each of the risk factors : Confusion, Urea 7 mmol / L, Respiratory rate ≥ 30 / min, low blood pressure, and Age ≥ 65 21 , and the 8-variable IDSA / ATS criteria 6 . We analyzed this study in accordance with the 8-variable IDSA / ATS criteria 6 , which is reported to have similar prognostic power to the Pneumonia Severity Index 20 in HCAP patients 22 , and disease severity on admission was identi ed as a prognostic factor for mortality from HCAP, as previously reported 23 .…”
Section: Discussionmentioning
confidence: 81%
“…First, in a Spanish study comparing HCAP and CAP patients with bacteraemic pneumococcal pneumonia, it was shown that despite low rates of inappropriate antibiotic therapy, mortality rates remained significantly higher in HCAP patients [13]. Secondly, in a Korean study, severity of illness, rather than type of pneumonia, was the main predicting factor for in-hospital mortality among patients with pneumonia hospitalised through the emergency department, despite a higher incidence of MDR in HCAP patients than CAP patients (29% versus 13%) [7]. Thirdly, in a large cohort study from 10 European countries including 119,699 patients admitted to the intensive care unit (ICU) for .2 days, excess risk of death for HCAP in the fully adjusted model ranged from 1.7 (95% CI 1.4-1.9) for drug-sensitive Staphylococcus aureus to 3.5 (2.9-4.2) for drug-resistant Pseudomonas aeruginosa.…”
mentioning
confidence: 94%
“…To date, eight studies specifically addressing HCAP have been published, including six retrospective [2][3][4][5][6][7] and two prospective studies [8,9], overall summing up to 2,056 patients. One study [8] has recently been extended to 557 patients [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported conflicting data on the frequency of multidrug-resistant bacteria [6,7,8,9,10,11]. Although patients who meet the criteria of HCAP are more susceptible to infection by drug-resistant pathogens, the majority of patients diagnosed with HCAP are not truly infected [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%